Netizen Views on Travel Reviews for Trip Selection: Pandangan Netizen terhadap Ulasan Perjalanan untuk Pemilihan Trip - Hartina Ayu Rosita; Nur Maghfirah Aesthetika (Academia Open, 2024)
This study delves into the evolving landscape of information and communication technology in Indonesia, examining the rapid progress and emergence of new technologies within the community. Focusing on Duapao.com, a travel agent utilizing both old and new technologies, the research investigates the influence of customer testimonials on netizens' perceptions of travel experiences. Utilizing Perception theory and qualitative research methods, the study explores five key indicators: essence, attention, expectation, motivation, and memory. The findings reveal that Duapao.com's online presence and positive testimonials significantly attract netizens, fostering interest and influencing their decision to experience the affordable and well-regarded travel promotions offered by the company. Highlights : Digital Influence: Duapao.com leverages the power of online testimonials to attract netizens and shape their perception of travel experiences. Rapid ICT Development: The study highlights the swift progression of Information and Communication Technology in Indonesia, impacting how communities engage with travel services. Affordability and Quality: Positive testimonials create a strong public perception of Duapao.com, emphasizing affordable travel promotions coupled with good service quality. Keywords : Duapao.com, Netizens, Travel Testimonials, Information and Communication Technology, Perception Theory